Examining soccer skill performance using a dual task paradigm - Latorre Román, P. Á.; Párraga Montilla, J. A.; Cabrera Linares, J. C.; Ramírez Lucas, J. M. (International Journal of Sports Science & Coaching, 2025)
The purpose of this study was to evaluate the reliability and validity of a holistic test (Soccer Skills and Cognitive Aptitude Test [SoSCAT]) that assesses soccer skills and performance in a dual-task (DT) context. A total of 73 male soccer players aged 12-18 years joined in this study. They were playing in three official Spanish regional leagues, and were divided according to their age into under 14 (U14, n = 25), under 16 (U16, n = 26), and under 18 (U18, n = 22). Additionally, players were categorized dichotomously into high-talented (n = 20) and lower-talented (n = 53) groups. Several soccer-skill and cognitive tests were evaluated. Regarding absolute reliability, the standard error of measurement (SEM) was 2.27 (5.30%) and the minimal detectable change (MDC) was 4.17 (9.75%). In relative reliability, the intra-class correlation coefficient was 0.908 (95% confidence interval [CI] = 0.826-0.951, p < 0.001). By category, the U18 group showed a higher performance in SoSCAT (p < 0.001) than U16 and U14. In addition, the DT cost (DTC) and Delta-Time were the lowest in the U18 group (p = 0.041). Moreover, the high-talent group showed the best performance in SoSCAT (p = 0.001), DTC (p < 0.001), and in Delta-Time (p < 0.001). To sum, the SoSCAT is a reliable tool for use under the DT context and it discriminates between levels of players and determines several variables that are relevant to soccer performance and that could help to early identify soccer talent.